Child labour trajectories of girls and adolescents in the cross-border region of Posadas (Argentina) - Encarnación (Paraguay) - Miño, María Gabriela (2024)
The main objective of this article is to analyze the relationship between gender and child labour trajectories, considering as a case study the situation of working girls and adolescents in the cross-border region connecting the cities of Posadas (Argentina) and Encarnación (Paraguay). To achieve this, the characterization outlines the activities carried out by women, emphasizing the significance of gender in the construction of social inequalities from childhood. Regarding its methodology, the study incorporates primary sources, including interviews with women and municipal and provincial administration officials with political responsibility on the subject; field observations and localized surveys; and structured information from open-access government statistics and articles from scientific repositories. In conclusion, it is suggested that girls and adolescents predominantly undertake household tasks. Furthermore, despite girls and adolescents also engaging in work outside the home – in businesses with family members or in street food vending – it is often boys of the same age who are tasked with solitary jobs that require strength, physical dexterity, and handling of monetary transactions.